Autonomic modulation and skeletal muscle oxygenation with intermittent low-load blood flow restriction knee extension - Garner, A. R.; Fanno, J. D.; McGrath, R.; Erickson, J.; Hackney, K. J. (Frontiers in Sports and Active Living, 2025)
Introduction: This investigation determined if an acute bout of low-load knee extension (KE) with intermittent blood flow restriction (BFR) influenced autonomic modulation and skeletal muscle oxygenation (SmO2%).